Créer un environnement interactif en classe de FLE - Kotuła, Krzysztof (Neofilolog, 2012)
Traditional communication in foreign language classes, even if varied by the use of diverse games and simulations, takes place in a sterile classroom environment, and therefore, is rarely encouraging. However, the new generation of pupils is growing up on computer games, and this fact is changing their expectations and demands on education. The dynamically changing virtual world of videogames may be the perfect environment for them to develop various skills. In this paper, I would like to present my preliminary conclusions made while implementing videogames into foreign language classes in a high school.